Al-Radhi,s comments, in his explanation to kafyat Ibn Al-hajeb, on Al-Andalusi-Alam addin Al-Lowraky (Damascus University Journal of arts and humanities sciences, 2023)
- Subject: "Revelation of Al-Radhi Al-Astrabady,s comments in his explanation to kafyat Ibn Al-hajeb, on Alam addin Al-Lowraky- Al-Andalusi declarations in his explanation to Al-Juzuliya ".- Aim: Illustration of Al-Radhi accordances to Al-Andalusi declarations, his replying and the judgments which he made.- Illustration of Al-Andalusi,s unilateral concerning opinion and transliteration.- The most important results were that Al-Radhi agreed with Al-Andalusi about twelve matters, and they disagreed in another seventeen matters (ones).- He adopted three judgment on some his declarations.- He showed aunique opinion and a uni- transliteration.
Keywords: comments; Al-Radhi,s comments; Al-Radhi,s comments, on Al-Andalusi